Identification of the main pathogens responsible for Healthcare-Related Infections in Neonatal Intensive Care Units: Integrative Review (Research, Society and Development, 2022)
Healthcare-Related Infections (ARs) account for one third of infant mortality. IRAS are acquired infections that occur during hospitalization and are often caused by Gram Negative Bacteria (BGN). The objective of this integrative review work was to identify the main microorganisms responsible for causing healthcare-related infections in patients hospitalized in neonatal intensive care units, in addition to identifying the sites of infection. A search was carried out for scientific articles published in the last 5 years indexed in the databases BVS/LILACS, BVS/MEDLINE, Science Direct, PUBMED. The following descriptors were used: “neonatal intensive care unit”, “bacteremia “infection nosocomial”. With these search strategies, it was verified whether there was occurrence in the title, abstract or keywords of scientific articles published in Portuguese, English and Spanish. After screening, 1186 eligible articles were selected for the research, of these, only 24 articles were selected for the research. Klebsiella spp. was the most common pathogen found in nosocomial infections, followed by Acinetobacter baumanii, Coagulase negative Staphylococcus (CoNS), Escherichia coli, Pseudomonas aeruginosa, the other microorganisms identified were identified with less clinical importance. The infections that were most prevalent in the studies were: bloodstream infection, catheter use and ventilator-associated pneumonia, with Klebsiella pneumoniae, Acinetobacter baumanni and Staphylococcus Coagulase negative as the main causative microorganisms.